2020
DOI: 10.1002/cncr.32903
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of an invasive leader cell–derived mutation cluster on chromosome 16q

Abstract: Background Intratumoral heterogeneity is defined by subpopulations with varying genotypes and phenotypes. Specialized, highly invasive leader cells and less invasive follower cells are phenotypically distinct subpopulations that cooperate during collective cancer invasion. Because leader cells are a rare subpopulation that would be missed by bulk sequencing, a novel image‐guided genomics platform was used to precisely select this subpopulation. This study identified a novel leader cell mutation signature and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…6B). Previously established leader-and follower-specific gene mutations were used to complement positional phenotypes to label each single cell, enabling for the first time, the combination of phenotypic, transcriptomic, and mutational analysis of single cells during active collective invasion 29,30 . We selected mutation loci from the list of leader-and follower-specific genes and verified that they had sufficient coverage in the single-cell sequences.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…6B). Previously established leader-and follower-specific gene mutations were used to complement positional phenotypes to label each single cell, enabling for the first time, the combination of phenotypic, transcriptomic, and mutational analysis of single cells during active collective invasion 29,30 . We selected mutation loci from the list of leader-and follower-specific genes and verified that they had sufficient coverage in the single-cell sequences.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…These results indicate that our NSCLC spatial localization is a coordinated patterning driven by genomic and epigenetic cellular profiles. At the RNA and protein levels, we found that underlying differences in their filopodia dynamics driven by a Jag1-Myo10 signaling axis further contribute to the stark differences in invasive capacities of the leaders and followers [28][29][30] . Similarly, invasive chains harbor metabolic heterogeneity, in which trailing followers are highly glycolytic and leaders depend upon mitochondrial respiration 27 .…”
Section: Application Of Sagamentioning
confidence: 88%
See 3 more Smart Citations